ANALISIS KADAR NITROGEN FOSFAT DAN KALIUM PADA GUANO KELELAWAR DI GUA ALAM SOWI DAN GUA ALAM GUNUNG MEJA MANOKWARI - Guntur A Solikhin; Ursula P Maker; Heru J Budiriato (Jurusan Biologi, FMIPA, Universitas Papua, 2023)
Guano is a bat’s droppings that are found in many caves and have been mixed with soil and decomposition bacteria. Bat’s guano can be used for alternative changer to chemical fertilizers, given its very large role in providing nutrients for soil’s fertility. This study aims to analyze the levels of nitrogen, phosphat and potassium in bat guano in the Sowi nature cave and Gunung Meja nature cave, Manokwari. The method used in this research is descriptive method. The procedure in this research are the preparation stage, the guano collection stage, the guano storage stage, the weighing stage, the packing stage, the shipping stage and the testing stage. The data obtained was compared between the two cave locations, presented in tables and described. The result testing levels of N, P and K in the Gunung Meja nature cave and Sowi nature cave, that levels of nitrogen (N) and Phosphate (P) in the Gunung Meja nature cave are higher than the Sowi nature cave, which is 8,21% nitorgen, 33,01% phosphate, while the level of potassium (K) in Sowi nature cave is higher at 2,62%.